ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI BAWANG MERAH LOKAL PALU DI DESA WOMBO KALONGGO KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Teang,Sulaeman, Miriam (AGROTEKBIS, 2015)
This study aims was to determine the affect of land area, seed, fertiliser and labor to the local Palu onion production in the Village Wombo Kalonggo Village Tanantovea Sub District Donggala Regency and the incomes of local palu union farming at Village Wombo Kalonggo Sub Tanantovea Donggala Regency. Respondents used in this study were 30 respondents of the 44 households that farming  of local palu union by using simple random sampling. The analisys showed that the simultaneously land area factor (X1), seeds (X1), fertilizer (X3) and labor (X4) very significant effect on farm production local palu union farming, with an F-count > F-table (1571,575 > 2,76) at the a level of 5% significancy. The test resuls show that the t-test was higly significant on land area with t-count > t-table (76.911 > 2,06), the seed was higly significant with t-count > t-table (15.843 > 2,06), fertilizer was highly significant with t-count > t-table (-10,640 > 2,06) and a significant on labor with t -count > t-table (2.604 > 2,06), respectively at the 5 % level ?. The revenue analysis results showed that the average income of the respondent of Local Palu onion farmers Wombo Kalonggo village in single growing season was Rp 6.359.362,23/0,53ha or Rp 11.998.796,66/ha.